An empirical study juxtaposing the importance of implementing an e-participation model by the government for compliance intention and satisfaction level among Djiboutian generation z - Aden, Kadir (Universitas Airlangga, 2023)
Abstract This research is among the very few studies seeking a focalized exploration of the impact of e-participation perception on satisfaction and compliance intention among the Djiboutian generation Z. To facilitate the task, our responders, which were encompassed of